Avaliação do caráter oxidante da violaceína - Leal, Angélica Maria de Sousa (2011)
Violacein is a violet pigment isolated from many gram-negative bacteria, especially from Chromobacterium violaceum, a betaproteobacterium found in the Amazon River in Brazil. It has potential medical applications as an antibacterial, fungicide, anti-tryptanocidal, anti-ulcerogenic and anti-cancer drug, among others. Furthermore, its pro-oxidant activity has been suggested, but only in two specific tumor lineages. Thus, in the present study, the prooxidant effects of violacein were investigated in both normal and tumor cells, seeking to evaluate the cell responses. The evaluation of violacein cytotoxicity using the Trypan blue dye exclusion method indicated that CHO-K1 cells were more resistant than tumor HeLa cells. The oxidative stress induced by violacein was manifested as an increase in intracellular SOD activity in CHO-K1 and MRC-5 cells at a specific concentration range. Nevertheless, a decrease was detected specifically at 6-12 μM in HeLa and MRC-5 cells. Interestingly, the increase in SOD activity was not followed by a concomitant increase in catalase activity. Regarding to oxidative stress biomarkers, increased protein carbonylation and lipid hydroperoxides levels were detected respectively in CHO-K1 and MRC-5 cells treated with violacein at 1.5-3 μM and 3 μM, which may be an evidence that this compound causes oxidative stress specifically in these conditions. Additionally, it is believed that the decline in cell viability observed in MRC-5 cells and HeLa treated with violacein at 6-12 M is due to mechanisms not related to oxidative stress. Moreover, the results suggested that violacein might cause oxidative stress by increasing endogenous levels of O2 -, since the occurrence of an expressive change in SOD activity. In addition, in order to evaluate the antioxidant activity of violacein in the absence of a biological system, the total antioxidant and iron chelating activity were evaluated, so that antioxidant activities were detected at 30 and 60 μM of violacein. Altogether, the results indicate that although oxidative stress is triggered by incubation with violacein, it did not seem to be high enough to cause serious damage to cell biomolecules in HeLa cells and only at specific concentrations in CHOK-1 and MRC-5 cells. Comparing the results obtained in cell culture and the in vitro antioxidant activity evaluation, the results confirmed that violacein presents opposing oxidant features when in presence or absence of a biological system and the antioxidant character only occurs at high concentrations of the pigment.